Factors that influence students' plans to take computing and information technology subjects in senior secondary school - Downes, Toni; Looker, Dianne (Computer science education, 2011)
This article explores factors that contribute to low participation rates in computing and information technology (CIT) courses in senior secondary school, particularly for females. Partly drawing on the Values-Expectancy Theory the following variables are explored separately and within a single model: gender, ability and values beliefs, access and use at home and at school. As well as presenting results consistent with current literature, an inclusive and eclectic model is developed. The model indicates that, in addition to gender and the student's beliefs about the value of the subjects, plans to take CIT subjects are also affected by the amount of use of IT at school. These school-related factors are inter-connected either directly or indirectly with students' beliefs about their IT abilities at both schooland home, as well as the amount of use at home. For educators who seek to improve participation rates, particularly for females, theidentification of school-related variables is encouraging, as the school - unlike the home - is a relatively accessible site of intervention.